2019
DOI: 10.1016/j.jtcme.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Wilhelm Brünings' forgotten contribution to the metabolic treatment of cancer utilizing hypoglycemia and a very low carbohydrate (ketogenic) diet

Abstract: The growing interest in the alterations of tumor cell metabolism and their possible therapeutic exploitation also spurred new complementary and integrative approaches such as treating patients with a ketogenic diet (KD). KDs aim at inhibiting glycolytic tumor metabolism and growth, and have therefore been proposed as adjuncts not only to standard-of-care, but also to other therapies targeting tumor metabolism. Here I describe the life and forgotten work of one of the earliest researchers who realized the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 100 publications
1
22
0
Order By: Relevance
“… 3 KDs for cancer patients are of particular interest as they mimic certain aspects of fasting without necessarily inducing an energy deficit and have a variety of applications against other chronic diseases. While the first documented clinical application of KDs against cancer dates back to Wilhelm Brünings’ seminal trials in head and neck cancer patients published In 1941/1942, 4 the scientific interest in using KDs for cancer treatment re-emerged only recently and is paralleled by an increasing interest on behalf of patients. For example, a recently published survey among high grade glioma patients revealed that almost three quarters (73%) of patients would be willing to try a KD for three months and 66% would participate in a clinical trial investigating the effectiveness of the KD.…”
Section: Introductionmentioning
confidence: 99%
“… 3 KDs for cancer patients are of particular interest as they mimic certain aspects of fasting without necessarily inducing an energy deficit and have a variety of applications against other chronic diseases. While the first documented clinical application of KDs against cancer dates back to Wilhelm Brünings’ seminal trials in head and neck cancer patients published In 1941/1942, 4 the scientific interest in using KDs for cancer treatment re-emerged only recently and is paralleled by an increasing interest on behalf of patients. For example, a recently published survey among high grade glioma patients revealed that almost three quarters (73%) of patients would be willing to try a KD for three months and 66% would participate in a clinical trial investigating the effectiveness of the KD.…”
Section: Introductionmentioning
confidence: 99%
“…KDs have recently attracted attention, with a broadspectrum approach aimed at lowering blood sugar and insulin levels, targeting the Warburg effect and fundamental genetic changes [60]. This dietary approach exploits the main Adapted from [90].…”
Section: The Emerging Role Of Ketogenic Diets (Kds) In Cancermentioning
confidence: 99%
“…The KD simulates fasting, increasing ketones in the blood and reducing glucose; fatty acid oxidation and acetyl-CoA production are also increased at high rates. KDs have recently attracted attention, with a broad-spectrum approach aimed at lowering blood sugar and insulin levels, targeting the Warburg effect and fundamental genetic changes [ 60 ]. This dietary approach exploits the main metabolic differences between micronutrient loss or limitation, mimicking fasting to some extent by lowering and stabilizing insulin levels, mildly elevating cortisol levels, and raising fatty acid oxidation.…”
Section: Modulating Metabolite Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…As the only clinical evidence in their case against the KD, the authors refer to a review by Klement about the seminal studies of Brünings during World War II in which cancer patients were treated with high doses of insulin and a very low carbohydrate diet. 2 Brünings initially observed tumor shrinkage, but in most cases, there was a rebound effect after 2-3 months. Israël and Schwartz suggest that after 2 months, a "ketogenic adaption" would have lead to production of ketone bodies which in turn would have supported tumor regrowth.…”
mentioning
confidence: 99%